(untitled) (Biological Sciences - PJSIR, 2023)
This study was conducted to evaluate the efficacy of alcoholic extracts of the bark and leaves of Eucalyptus spp., Mentha virdis, Mentha lognifolia, Capsicum annuum and Dodonaea viscosa, with the compatibility study between the biocidal Naturalis-L (Beauveria bassiana) and the alcoholic extract of Dodonaea against adults of black aphid Aphis fabae Scopoli under laboratory conditions. The results showed the superiority of the extract of the Dodonaea plant in causing the highest rates of killing and was significantly superior to the rest of the other treatments, where the concentration of 3000 ppm achieved the highest mortality rates which reached 66.67, 86.67 and 93.33% after 24, 48 and 72 h of treatment under laboratory conditions. The results showed that the extracts of hot pepper plant at the concentration of 3000 ppm caused mortality of 56.67, 83.33 and 91.33% under the same time period. The results of evaluating the compatibility of the commercial preparation Naturalis-L with the alcoholic extract of the Dodonaea plant showed that the concentration (3 mL + 3000 ppm) was caused high mortality 96.33% after 72 h of treatment.